FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS DENGAN GENDER SEBAGAI VARIABEL MODERATOR PADA BUMN TERBUKA PERIODE 2016-2020 - Riska Dayu Rizky; Ali Mutasowifin (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
BUMN (state owned enterprise) as a business unit with most of the capital owned by the government has the main goal of obtaining a profit from the activities it carries out. This study aims to analyze the factors that influence the profitability of state-owned companies with gender as a moderating variable. The sampling method used is non-probability sampling with a purposive sampling technique. The samples generated from purposive sampling are 16 companies. The study used panel data regression analysis. The results showed that variables Current Ratio, Debt to Equity Ratio, and Growth Sales do not significantly influence ROA. The results of the moderation regression test showed that the gender variable does not have a moderating effect on the Current Ratio, Debt to Equity Ratio, and Growth Sales variables on ROA.